Microstructure Influence on Rock Electrical Properties: Integration of Laboratory and Numerical Methods - Muhammad Bisri Mustofa; Aditya A. Wicahyanto; Firda Mahfuziahaq; Supriyanto Supriyanto (Lembaga Ilmu Pengetahuan Indonesia, 2024)
The electrical properties of rocks are widely used in characterizing reservoir rocks due to their ability to identify porosity, fluid types, and saturation levels. This study aims to determine the effect of microstructure on the electrical properties of Ngrayong Formation rocks through laboratory measurements and numerical calculations. Twelve samples from three-grain size categories with porosity ranges of 34-48% were prepared for resistivity measurements under partially and fully brine-saturated conditions using a 6% NaCl solution. Scanning results of the three categories revealed that grain size influences the microstructure of rocks, including the distribution of grain size and pore size. The estimated electrical properties show that at low saturation, microstructure significantly affects resistivity response. Conversely, at high saturation, variations in microstructure tend to result in uniform resistivity, indicating minor microstructural influence on high-saturation electrical property estimations. Additionally, Archie parameters were determined with ranges of 2.1-3.4 for the cementation exponent and 1.2-2.4 for the saturation exponent. A strong correlation was also observed between laboratory measurements and numerical calculations, especially for samples with small grain sizes. This study provides a deeper understanding of the electrical properties of rocks as a function of their microstructure, which can serve as a base for interpreting electrical data from Routine/Special Core Analysis, resistivity log data, or field resistivity data in Applied Geophysics.